Dietary Supplements Contributed Substantially to Total Intakes and Nutritional Adequacy of Several Micronutrients Among U.S. Adults, NHANES 2011–2014 (OR14-07-19). (13th June 2019) - Cowan, Alexandra; Jun, Shinyoung; Bhadra, Anindya; Dodd, Kevin; Dwyer, Johanna; Eicher-Miller, Heather; Gahche, Jaime; Potischman, Nancy; Tooze, Janet; Bailey, Regan
Abstract: Objectives: To estimate total mean usual micronutrient intakes (inclusive of dietary supplements (DS)), Dietary Reference Intakes (DRI) adherence, and the % contribution of DS to total usual micronutrient intakes for U.S. adults (≥19y) using data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES, n = 9474), by sex, age, and race and Hispanic origin groupings. Methods: Dietary data were collected using two 24-hour recalls; DS data was collected via an in-home 30-day questionnaire that ascertained participants' usage in the past 30 days. The National Cancer Institute Method was used to estimate mean total usual micronutrient intakes and the proportion of the population complying with DRI by population subgroups: sex, age, and race and Hispanic origin. Results: DS contributed substantially to meeting the DRI recommendations for several key nutrients, including calcium, magnesium, folate, zinc, and vitamins C, D, B6, and K in both men and women. However, approximately half of U.S. adults still failed to meet the estimated average requirement (EAR) for magnesium (45%), and vitamins C (35%), K (45%), and D (63%), even with the inclusion of DS. The proportion of total usual intakes < EAR was significantly higher in men than women for magnesium (46 v 42%) and vitamins C (39 v 32%), and D (66 v 59%). In both men and women, total intakes of folate, zinc, and vitamins A, D, and B12 increased with age. Vitamin D from DS contributed the most towards total intake for most sex and age groups, with the largest contribution being in older women (84%). Non-Hispanic (NH) Blacks and Hispanics had significantly lower total intake of vitamin D than those of NH Whites and Asians, while NH Whites and Hispanics had significantly higher total intakes of calcium than their NH Black and Asian counterparts. Conclusions: Adherence to DRI recommendations for nutrient intake differs significantly by sex, race and other demographic characteristics. Dietary supplements substantially contribute to total intakes for several micronutrients among users; however, many population subgroups continue to be at risk for inadequacy for key nutrients. Funding Sources: This work was supported through the National Institutes of Health.